Effects of Tibial Rotational–guided Growth on the Geometries of Tibial Plateaus and Menisci in Rabbits. Issue 6 (July 2019) - Sevil-Kilimci, Figen; Cobanoglu, Mutlu; Ocal, Mehmet K.; Korkmaz, Deniz; Cullu, Emre
Abstract : Background: There are studies on the use of oblique plate over epiphyses for rotational deformities but the effects of this method on bone are not yet known. The purpose of this study was to determine the effect and rebound effect of rotational-guided growth on the geometries of the tibial plateaus and menisci in a rabbit model of tibial axial rotation. Methods: Thirty male rabbits were 6 weeks old when medial and lateral plates were applied to the proximal tibias of the left side. After 4 weeks, 15 rabbits were euthanized (group 1), and the plates from the tibias of the remaining 15 rabbits (group 2) were removed. The rabbits in group 2 were euthanized 4 weeks later. Results: In the rabbits of group 1, the most striking differences were a decrease in the lateral tibial slope (from 28.3 to 10.8 degrees) and decrease in the ratio of the lateral plateau covered by the meniscus (from 71.9% to 61.3%). After removing the plates (group 2), the observed values of the rebound effects were 25.9 and 29.8 degrees for the lateral tibial slope, and 76.5% and 77.2% for the ratio of the lateral plateau covered by the meniscus. However, the meniscal geometries continued to change. Conclusions: The rotational-guided growth provided by using plates caused a change in the tibial plateau geometry, and the rebound effect, except in the meniscal geometry, was observed after removing the plates in the growing period of the rabbits. Rotational-guided growth for the restoration of tibial axial rotation deformities may be suggested after determining the clinical effects of the increasing meniscal variables. Level of Evidence: Clinical relevance: the rotational-guided growth needs close follow-up because of possible changes in anatomy of the bone.